GREEN TRAINING, GREEN PROJECT AND GREEN CONSTRUCTION AS ANTECEDENTS OF CUSTOMER SATISFACTION: EXAMINING THE MEDIATING ROLE OF GREEN SUPPLY CHAIN MANAGEMENTGREEN TRAINING, GREEN PROJECT AND GREEN CONSTRUCTION AS ANTECEDENTS OF CUSTOMER SATISFACTION: EXAMINING THE MEDIATING ROLE OF GREEN SUPPLY CHAIN MANAGEMENT - Mee-ngoen, Benjabhon; Nualkaw, Suwat; Sirariyakul, Tussanee; Tomcharoen, Narong; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2020)
The prime objective of the present study is to examine the impact of green project, green construction and green training of the employees on the customer satisfaction. Moreover, the mediating role of green supply chain management is examined among the mentioned variables as well. In order to collect the data, 476 self-administered questionnaires were distributed among the customers of construction industry of Indonesia. The response rate was 84%. Moreover, in this research, the adoption of PLS path modelling for hypotheses testing was done because of multiple reasons. The findings of the study accepted all proposed hypothesis. It shows that construction firms should focus on their environmentally friendly activities to make the customer satisfied. The findings of the study are important for the practitioners and policy makers of the construction industry by which they can make the customer satisfied through meeting the expectations of the customers. Furthermore, present study fills the gap of limited studies addressing environmental issues in supply chain.